Muslim And Hindu Women’s Inheritance Rights in Bangladesh: An Empirical Study - Asrafuzzaman, A B M; Sultana, Shirin; Hasan Sawon, Rubiaat (South Asian Journal of Social Sciences and Humanities, 2025)
This study aims to examine the status of Muslim and Hindu women’s inheritance issues in  Bangladesh through empirical research. The empirical study aims to investigate the perceptions  of ordinary people (both men and women) regarding inheritance issues, in conjunction with  expert observations, and to assess the impact of such perceptions on women’s empowerment  and the country's development agendas. Based on the empirical findings, the study suggests  some workable solutions that the Government may consider to ensure gender equality and fulfill its commitments under the SDGs.
Keywords: Muslim and Hindu Women; Inheritance; Gender Equality; Empowerment; SDGs